Model provenance tracking and inference for integrated environmental modelling. (October 2017) - Zhang, Mingda; Yue, Peng; Wu, Zhaoyan; Ziebelin, Danielle; Wu, Huayi; Zhang, Chenxiao
Abstract: Integrated environmental modeling (IEM) provides a systematic way to couple models for integrated analysis. Coupled models in IEM often exchange data at runtime for time-step based executions. It is a challenge to track which raw observations or intermediate data exchanged at runtime contribute to individual model outputs. Time-step level provenance is needed to audit the trail of model execution or perform diagnosis in case of anomalies. This paper introduces a method to support provenance awareness in IEM. It suggests that individual models should expose necessary interfaces for provenance capturing in IEM environments. The provenance is represented using the W3C PROV model for interoperability. Fine-grained provenance is inferred based on coarse-grained provenance and temporal characteristics of computations of numerical time marching models. The approach is implemented in OpenMI-compliant models. A case study of model provenance tracking and inference on the watershed runoff simulation scenario illustrates the applicability of the approach. Highlights: Model provenance tracking in integrated environmental modelling. Inference for fine-grained model provenance. Provenance awareness for OpenMI.